Mesenchymal stromal cells in skin wound healing - Hertel, Fernanda Campos (2019)
Wound healing is a multi-orchestrated process with overlapping phases, called hemostasis / inflammation, proliferation and remodeling, and is influenced by controlled biological and molecular events, with growth factors, cytokines, cells and extracellular matrix. The difficulty of wound repair is common and has become a global problem with large financial costs, associated with long treatment and withdrawal from work, often requiring hospitalization, as well as the personal cost to the patient and family members involved. Research to new methods such as tissue engineering and regenerative medicine, aimed at reducing recovery time, related costs and improving tissue regeneration. In this context, cell therapy, especially mesenchymal stromal cells (MSCs), has shown great potential for wound healing. The strong ability to proliferate and differentiate, and its immunomodulatory effects are the main characteristics for regenerative medicine, related to its paracrine effect by the secretion of growth factors and cytokines. The objective with this work was to evaluate the influence of adipose tissue-derived mesenchymal stromal cells (ASC) on wound repair, using platelet-poor plasma (PPP) to promote cell adhesion in the wound, as well as discussing the main components of the repair process and how MSCs can influence their actions. In this study, ASCs were associated with PPP for cutaneous wounds of rabbits, and their actions were assessed by macroscopic and histopathological analysis. Our results suggest this association were able to accelerate epithelialization and wound healing in the early stage of proliferation and increased cellular infiltrate in the late stage of proliferation. In addition, PPP alone showed a more mature granulation tissue compared to the control and ASC + PPP groups, suggesting a new method for wound therapy.